Analisis SWOT terhadap Strategi Transformasi Digital Aplikasi PLN Mobile dalam Meningkatkan Kualitas Pelayanan Pelanggan di PLN (Persero) Unit Pelaksana Pelayanan Pelanggan (UP3) Malang, Unit Layanan Pelanggan (ULP) Batu. - Nuriyanto, Agung Rachmad; Basalamah, Muhammad Ridwan; Rahmawati, Rahmawati (E-JRM : Elektronik Jurnal Riset Manajemen, 2025)
Abstract This research, titled "SWOT Analysis of Digital Transformation Strategy of PLN Mobile Application in Improving Customer Service Quality at PLN (Persero) UP3 Malang, ULP Batu," evaluates the digital transformation strategy through PLN Mobile in enhancing customer service. Using SWOT analysis, the study identifies the strengths, weaknesses, opportunities, and threats associated with the application’s implementation and its impact on service effectiveness. The findings indicate that PLN Mobile has significant potential to enhance service quality, leveraging internal strengths and opportunities while addressing weaknesses and threats. Recommended strategies include integrating financial services, enhancing data security, fostering innovation to counter competition, increasing user adoption through social campaigns and feedback, and improving digital literacy while diversifying services to mitigate external risks. This research highlights the critical role of digital transformation in PLN's customer service improvements, as PLN Mobile has received positive public feedback for its ease of use and quick response to complaints. The study’s insights serve as a valuable reference for PLN in further developing a more efficient and responsive customer service system to meet future demands. Keywords: SWOT Analysis, Digital Transformation Strategy, PLN Mobile Application, Improving Customer Service Quality